2017
DOI: 10.1038/s41598-017-10073-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Image Analysis To Evaluate Subvisible Particles During Continuous Drug Infusion In a Neonatal Intensive Care Unit

Abstract: Studies have shown that infused particles lead to numerous complications such as inflammation or organ dysfunctions in critically ill children. Nevertheless, there is very little data available to evaluate the amount of particulate matter potentially administered to patients, and none with regard to infants. We have investigated the quantity received by these patients during multidrug IV therapies. Two different protocols commonly used in our neonatal intensive care unit (NICU) to manage excessively preterm in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…The study also indicated however that patients can receive up to 900,000 particles per day during hospitalisation despite these infusion systems, which caused us to turn our attention to in-line filtration. Neonatal and pediatric populations receiving a great number of particles, especially large ones, are particularly affected as shown in a previous study 3 . These may cause serious damage to the body, especially large particles of about 10 µm in diameter 4 .…”
Section: Introductionmentioning
confidence: 59%
“…The study also indicated however that patients can receive up to 900,000 particles per day during hospitalisation despite these infusion systems, which caused us to turn our attention to in-line filtration. Neonatal and pediatric populations receiving a great number of particles, especially large ones, are particularly affected as shown in a previous study 3 . These may cause serious damage to the body, especially large particles of about 10 µm in diameter 4 .…”
Section: Introductionmentioning
confidence: 59%
“…In our case, the particulate load was evaluated over a 6-h infusion period which can be extrapolated to a 24-h period and our results show lower particulate contamination than observed in previous studies [ 13 , 14 ]. Perez et al investigated the number of particles received by preterm infants over 24 h during multidrug IV therapies [ 13 ]. Two different protocols commonly used in an NICU were reproduced in vitro and analysed with the same equipment as that described in our study.…”
Section: Discussionmentioning
confidence: 59%
“…Our study is the first to quantify the particulate matter potentially administered to critically ill adult patients during a standard infusion protocol for the treatment of septic shock or acute respiratory distress syndrome. Previous studies have explored particulate contamination during leukaemia treatment in children [ 14 ] and NICU multidrug IV therapies [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations